Comparative Study of Grit and Self-Esteem among NCC Cadets and Non-NCC Students At Undergraduate level - Vaishnavi V; Sreenivas M (Journal of Psychology and Social Sciences, 2026)
The National Cadet Corps (NCC) of India provides structured military-style training that may differentially shape psychological attributes in youth. This study examined whether NCC enrollment was associated with higher levels of grit and self-esteem relative to non-enrolled peers. A total of 324 young adults (130 female, 194 male) were recruited through purposive sampling: 166 active NCC cadets and 158 non-enrolled students from higher educational institutions specifically the under graduate level in India. Grit was measured using the 12 item Grit Scale (Grit-S; Duckworth & Quinn, 2009) and self-esteem using the 10 item Rosenberg Self-Esteem Scale (RSES; Rosenberg, 1965). Independent-samples t-tests and Mann–Whitney U tests confirmed significant group differences on both variables. NCC cadets reported substantially higher grit scores (M = 3.55, SD = 0.895) than non-NCC participants (M = 2.39, SD = 0.892), t(322) = −11.70, p < .001. Similarly, NCC cadets exhibited markedly higher self-esteem (M = 31.75, SD = 4.38) compared to non-NCC participants (M = 17.91, SD = 4.96), t(322) = −26.60, p < .001. Frequency analyses revealed that 80 NCC cadets (48.2%) fell in the high-grit category, while 91 non-NCC participants (57.6%) fell in the low-grit category. Gender-based distributions were also explored and reported descriptively. These findings suggest that structured military-affiliated training environments may foster perseverance and positive self-regard in youth. Implications for character development programmes and positive psychology interventions in India are discussed.